Closed rupture of the posterior tibial artery secondary to a soccer injury. - Tytherleigh, M. G. (Royal College of Surgeons of England, 1998)
Arterial damage following blunt trauma is uncommon and is usually the result of high-energy injury. We report a case of posterior tibial artery rupture after a closed distal tibial fracture, sustained during a low-energy soccer tackle.